Web development and Internet Technologies - iBook Development Group (Philippines : iBook Publishing, 2011)
The modern world has opened new vistas almost in all the fields of human life. The domain of information technology is witnessing innovations and developments at a rapid pace. Education is one of them which have potential to enrich and motivate the students to take up the challenges in life. Working hand and hand, theses two can provide limitless possibilities as we break into a an era where advancement occurs one after the other and knowledge is at everyone's fingertips.
Includes bibliography
English Text
Keywords: Computer Programming